Taking the Time: D.I.Y. Filmed Portraits for the GLAM Sector - Cunningham, Ross (Auckland University of Technology, 2018)
This practice-based Master of Philosophy project involves the design, production and dissemination of four filmed portraits of four individual New Zealand musicians. The increasing use of websites within the GLAM (Gallery, Library, Archive and Museum) sector to tell stories about their collections and build relationships with their communities has created new opportunities for story-tellers to produce digital stories about our culture. This study engages with those opportunities to design, produce and disseminate four biographical portraits of four artists, told in their own words. The project revolves around three key themes: D.I.Y. (do-it-yourself) approaches to the creation of creative works; the telling of first-person biographical stories of artists; and the utilisation of digital technology within the GLAM sector. The portraits produced consist of long-form filmed interviews with each artist, filmed on an iPhone and edited using domestically licenced editing software. Strategies and conventions from the literary, fine art and music worlds, as well the screen world, informed the design and production of the portraits. The completed portraits are now available to the public via the New Zealand music website AudioCulture. The D.I.Y. method applied to the production of these portraits offers a technical and conceptual approach to the production of first-person filmed portraits that could be applied to people other than artists, disseminated by organisations beyond the GLAM sector, and be applied by other story-tellers. The portraits are designed to offer a window into the lives of these artists for future generations as well as those of today, so that the work and lives of these artists is remembered.
Keywords: Portraiture; Biography; D.I.Y.; GLAM; Documentary; New Zealand; Music; Audioculture